Quality management in imaging diagnosis and the nursing team: a case study - Laura Vargas Acauan; Juana Macias Seda; Graciele Oroski Paes; Marluci Andrade Conceição Stipp
ABSTRACT Objective: to know the contributions of nursing in the implementation of the quality management principle of the accreditation program in imaging diagnosis. Methods: a single, qualitative case study carried out in an accredited radiology and imaging diagnosis service. The data collection took place through semi-structured interviews, direct observation, and documentary analysis with the support of software in organizing the data for analysis. Results: a total of four thematic units emerged: the accreditation process in imaging services, the implementation of the program, the role of nursing in imaging services and patient safety and the management of non-conformities in imaging services. Of the other data sources, the word risk was highlighted and a non-conformity was evidenced in the external audit. Final considerations: nursing contributed mainly to the management of the risks involved in the performance of imaging and patient safety tests, requirements of the quality management principle of the accreditation program.